Development of computational method for detection of the object’s near-zero apparent motion on the series of ccd-frames - Khlamov, Sergii; Savanevych, Vadym; Briukhovetskyi, Olexsander; Oryshych, Serhiy (Eastern-European Journal of Enterprise Technologies, 2016)
A computational method for detecting near-zero apparent motion of objects on the series of CCD-frames using the XY-wise and coordinate-wise decision rules is developed. The method is based on checking the statistical significance of the factor of speed of the object apparent motion on the studied series of measurements using the Student’s t-test for coordinate-wise decision rules and F-test for XY-wise decision rules. This is the main feature of the developed computational method compared with the conventional decision rules based on the maximum likelihood criterion. The developed computational method for detecting near-zero apparent motion of the objects was tried and tested, and embedded in the block of inter-frame processing of the CoLiTec software package for the operational automated detection of new and tracking of the known asteroids, comets and faint celestial bodies. Using the CoLiTec software package and the proposed embedded computational method, the comet C/2012 S1 (ISON) — long-period sungrazing comet was discovered, which at the time of discovery was the object with near zero apparent motion.